2019
DOI: 10.1007/s42106-019-00062-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cereal Monoculture and Tillage Systems on Grain Yield and Weed Infestation of Winter Durum Wheat

Abstract: This experiment aimed at evaluating the yield and weed infestation of winter durum wheat grown in a multi-year cereal monoculture (CM) and crop rotation (CR) as well as in three tillage systems: (1) conventional tillage-CT, (2) reduced tillage-RT, and (3) no-tillage-NT. Shallow ploughing and pre-sowing ploughing were performed in the CT system; a cultivator and a cultivating set were used in the RT system, whereas glyphosate and a cultivating set were applied in the NT system. Grain yield was lower in CM than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
9
21
1
Order By: Relevance
“…The lower TGM values under RT and NT systems may have been related to soil surface compaction, less rainwater penetration into the soil, and water stress at the grain filling stage, as both treatments received lower moisture than in CT. Similar results have been reported regarding reduced TGM values with decreasing tillage level by Wozniak et al [40] and Wozniak [37] for wheat, by Wozniak and Soroka [35] for triticale, and by Wozniak and Gaweda [33] for pea plants. Wozniak et al [40] reported a significant difference of TGM for wheat grains in tillage treatments with mean values of 42.3 g, 41.5 g, and 40.4 g for CT, RT, and NT systems, respectively.…”
Section: Wheat Grain Yield and Yield Componentssupporting
confidence: 90%
See 1 more Smart Citation
“…The lower TGM values under RT and NT systems may have been related to soil surface compaction, less rainwater penetration into the soil, and water stress at the grain filling stage, as both treatments received lower moisture than in CT. Similar results have been reported regarding reduced TGM values with decreasing tillage level by Wozniak et al [40] and Wozniak [37] for wheat, by Wozniak and Soroka [35] for triticale, and by Wozniak and Gaweda [33] for pea plants. Wozniak et al [40] reported a significant difference of TGM for wheat grains in tillage treatments with mean values of 42.3 g, 41.5 g, and 40.4 g for CT, RT, and NT systems, respectively.…”
Section: Wheat Grain Yield and Yield Componentssupporting
confidence: 90%
“…As stated by many researchers, in the conventional tillage and conservation tillage systems, the yield and quality parameters of crops are functions of the interactions of many parameters, which are difficult to predict [34][35][36]. Generally, from the review of the results of research studies conducted in this paper, it can be stated that when reducing the levels of tillage from the conventional system to conservation tillage systems (RT or NT systems) in cereals, there is a decrease in crop yield [37]. The soil tillage system also affects the quality parameters of grains, such as the physical dimensions and chemical composition [34,38,39].…”
Section: Introductionmentioning
confidence: 94%
“…This area was marked at random (twice) using a frame 0.5 × 1.0 m in size. The air-dry weight of weeds was determined by collecting all weeds from the frame area, removing their root system, and keeping them in a well-ventilated room until their constant weight has been achieved (Woźniak and Soroka 2017).…”
Section: Yield Components and Statistical Analysismentioning
confidence: 99%
“…(Honsdorf et al, 2019). The results of Woźniak (2020) showed that zero tillage is more effective under dry climatic conditions, while its effectiveness in rainy seasons decreases.…”
Section: Introductionmentioning
confidence: 99%